2022
DOI: 10.12998/wjcc.v10.i3.929
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture at ghost points combined with fluoxetine in treating depression: A randomized study

Abstract: BACKGROUND Depression affects more than 350 million people worldwide. In China, 4.2% (54 million people) of the total population suffers from depression. Psychotherapy has been shown to change cognition, improve personality, and enhance the ability to cope with difficulties and setbacks. While pharmacotherapy can reduce symptoms, it is also associated with adverse reactions and relapse after drug withdrawal. Therefore, there has been an increasing emphasis placed on the use of non-pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Studies have shown that acupuncture combined with drug treatment for depression can improve the depressive state and physical symptoms of patients with depression. Compared with drug use alone, acupuncture combined with drug treatment has been shown to improve efficacy, reduce adverse reactions, and reduce drug dose[ 9 ]. Acupuncture at effective thirteen ghost points is used in traditional Chinese medicine to treat emotional diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that acupuncture combined with drug treatment for depression can improve the depressive state and physical symptoms of patients with depression. Compared with drug use alone, acupuncture combined with drug treatment has been shown to improve efficacy, reduce adverse reactions, and reduce drug dose[ 9 ]. Acupuncture at effective thirteen ghost points is used in traditional Chinese medicine to treat emotional diseases.…”
Section: Introductionmentioning
confidence: 99%